Evaluation of Indomethacin Stability - Dilla, Anita Ratna; Karneli, Supriyadi (East Asian Journal of Multidisciplinary Research, 2024)
Indomethacin is a non-steroidal anti-inflammatory drug (NSAID) that is most often used to treat inflammation and pain due to rheumatic diseases. Forced degradation is carried out to save time in carrying out contamination analysis on pharmaceutical preparations. Forced degradation is carried out by providing extreme exposure conditions. The aim of this research is to determine whether indomethacin is stable under various degradation conditions such as acid, base, oxidation, photolysis and temperature. The HPLC method is the main choice because it can simultaneously separate compounds, identify compounds and measure concentrations. The mobile phase used was formic acid: acetonitrile (55:45), C18 column with a flow rate of 1.5 ml/minute and a wavelength of 240 nm. The results of this research show that the validation of Indomethacin meets the validation requirements which include selectivity, linearity, precision, accuracy, LOD, LOQ, and resilience. Indomethacin stability tests under acidic, alkaline, oxidation, photolysis and temperature conditions found that Indomethacin was unstable under all conditions.